Chemistry Mobile Learning of Chemical Elements to Foster Education for Sustainable Development - Zidny, Robby; Yudanto, Cavela Az-zahrah; Aisyah, Ratna Sari Siti; Li, Baoyu (Jurnal Tadris Kimiya, 2025)
Students often face difficulties in learning chemical elements due to the large number of concepts that require memorization and limited contextual engagement. At the same time, chemical elements play a vital role in addressing environmental issues, making their understanding essential for advancing Education for Sustainable Development (ESD). This study aimed to develop an Android-based Chemistry Mobile Learning (CML) application in the form of an educational game to promote ESD-oriented chemistry learning. The development followed the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The CML application was validated by six expert reviewers, resulting in Aiken’s V scores of 0.91 and 0.93, indicating a high level of validity. Student feedback showed that 91% rated the learning experience as “Very Good.” The results suggest that the developed CML tool is both feasible and practical for classroom implementation. It enhances student engagement, supports meaningful learning, and fosters sustainability-oriented thinking in chemistry education.